A Study of Secure Data Storage Analysis in Cloud Computing - Bunkar, Rajesh Kumar; Mishra, Dr Bharat; Rai, Dr. P.K (IJRDO -Journal of Computer Science Engineering, 2015)
Cloud computing is an identical IT capacity (services, software, or infrastructure) delivered via internet technologies in a pay-per-use, self-service way. Cloud storage based file management services, such as DropBox, Google Drive, OneDrive and Mega, are worldwide resource used by millions of users. Features for rising of outer file systems with DropBox, FTP and GoogleDrive facilitate users have all their file sync and distribute tools in a single interface. Cloud storage like DropBox, Google Drive, OneDrive and Mega Cloud to trust our data on other people’s data centre. OwnCloud is open source file sync and share can keep our data on our servers and decide what other public cloud services we want to integrate into personal cloud of cloud storage size, security, and used in platform between online public cloud as OneDrive, GoogleDrive, DropBox, Mega, and private cloud storage OwnCloud with public cloud OpenShift and some file related storage analysis between them.